Evaluation of Prebiotic Potential of Crude Polysaccharides Extracted from Wild Lentinus polychrous and Lentinus squarrosulus and Their Application for a Formulation of a Novel Lyophilized Synbiotic - Marutpong Panya; Chamraj Kaewraemruaen; Phairo Saenwang; Patcharin Pimboon (Foods, 2024)
Edible mushrooms, including wild mushrooms, are currently being investigated as natural sources to evaluate their prebiotic potential. This study aimed to evaluate the prebiotic potential of crude polysaccharides (CPSs) extracted from wild Lentinus squarrosulus UBU_LS1 and Lentinus polychrous UBU_LP2 and their application as cryoprotectants in the freeze-drying process to formulate a novel synbiotic product. Based on fruiting body morphology and molecular identification, two wild edible mushrooms named UBU_LS1 and UBU_LP2 were identified as Lentinus squarrosulus and Lentinus polychrous, respectively. L. squarrosulus UBU_LS1 and L. polychrous UBU_LP2 contained high amounts of CPS after hot water extraction. Monosaccharide component analysis showed that CPS_UBU_LS1 and CPS_UBU_LP2 were typical heteropolysaccharides. CPS_UBU_LS1 and CPS_UBU_LP2 showed hydrolysis tolerance to the simulated human gastric acidic pH solution, indicating that these CPSs are capable of reaching the lower gastrointestinal tract. Antioxidant activity determined using the 1,1-diphenyl-2-picrylhydrazyl assay revealed that the CPS_UBU_LS1 and CPS_UBU_LP2 displayed greater antioxidant activity comparable with that of ascorbic acid. It was found that CPS_UBU_LS1 and CPS_UBU_LP2 have a high potential for stimulating growth in all probiotic strains. Moreover, both CPS compounds could possibly be used as cryoprotectants in freeze drying, since the viability of the selected probiotic L. fermentum 47-7 exhibited cell survival of greater than 70% after 90 days of storage at 4 °C. These results highlight that wild edible mushrooms L. squarrosulus UBU_LS1 and L. polychrous UBU_LP2 are potential natural sources of prebiotics and can be applied as cryoprotectants in the freeze-drying process. The crude polysaccharide derived from this study could also be considered as a potent antioxidative compound. Therefore, our study provides evidence to support the application of CPSs from wild edible mushrooms in synbiotic product development and in various functional foods. Finally, further evaluation of these prebiotics, including the determination of the potential rehabilitation of beneficial gut microbes in diseased individuals, is currently being conducted by our research group.